T.S. Eliot and the ideology of Four quartets - Cooper, John Xiros 1944- (Cambridge University Press, 1995)
Criticism of Eliot has ignored the public dimension of his life and work. His poetry is often seen as the private record of an internal spiritual struggle. Professor Cooper shows how Eliot deliberately addressed a North Atlantic 'mandarinate' fearful of social disintegration during the politically turbulent 1930s. Almost immediately following publication, Four Quartets was accorded canonical status as a work that promised a personal harmony divorced from the painful disharmonies of the emerging postwar world. Cooper connects Eliot's careers as banker, director and editor to a much wider cultural agenda. He aimed to reinforce established social structures during a period of painful political transition. This powerful and original study re-establishes the public context in which Eliot's work was received and understood. It will become an essential reference work for all interested in a wider understanding of Eliot and of Anglo-American cultural relations